Annual update in intensive care and emergency medicine. 2011. - Vincent, J. L.; SpringerLink (Online service). (Berlin Heidelberg New York Springer, 2011)
The Annual Update compiles the most recent developments in experimental and clinical research and practice in one comprehensive reference book. The chapters are written by well recognized experts in the field of intensive care and emergency medicine. It is addressed to everyone involved in internal medicine, anesthesia, surgery, pediatrics, intensive care and emergency medicine.
Part I: Mechanisms of Sepsis and Multiple Organ Failure -- Part II: Coagulation System -- Part III: Acute Respiratory Failure -- Part IV: Endotracheal Intubation -- Part V: Ventilator Issues -- Part VI: Cardiac Crises -- Part VII: Renal Aspects -- Part VIII: Fluids -- Part IX: The Microcirculation -- Part X: Cardiovascular Monitoring -- Part XI: Perioperative Medicine -- Part XII: Infection and Sepsis -- Part XIII: Liver Failure -- Part XIV: Trauma and Emergency Medicine -- Part XV: Neurological Aspects -- Part XVI: Metabolic Disorders and Nutrition -- Part XVII: ICU Organization and Management -- Part XVIII: The Future.
Electronic reproduction.
Keywords: Critical care medicine; Emergency medicine; Intensive care; Emergency medicine; Electronic books